Infectious ideas: modelling the diffusion of ideas across social networks - Haggith, M.; Prabhu, Ravi; Colfer, C.J.P.; Ritchie, B.; Thomson, A.; Mudavanhu, H. (2003)
Will the practice of collecting wild honey wearing no clothes become a widespread practice in Zimbabwe? Or will beekeeping take over as the main way that people acquire honey? Both practices impact on forest resources; how can the foresters influence the uptake of these ideas?. This paper describes an exploratory modelling study investigating how social network patterns affect the way ideas spread around communities. It concludes that increasing the density of social networks increases the spread of successful ideas whilst speeding the loss of ideas with no competitive advantage. Some different kinds of competitive advantage are explored in the context of forest management and rural extension.